Sixty years of anthropogenic pressure: a spatio-temporal genetic analysis of brown trout populations subject to stocking and population declines - Hansen, Michael M; Fraser, Dylan J; Meier, Kristian; Mensberg, Karen-Lise D (Molecular ecology, 2009)
Analyses of historical samples can provide invaluable information on changes to the genetic composition of natural populations resulting from human activities. Here, we analyse 21 microsatellite loci in historical (archived scales from 1927 to 1956) and contemporary samples of brown trout (Salmo trutta) from six neighbouring rivers in Denmark, to compare the genetic structure of wild populations before and after population declines and stocking with nonlocal strains of hatchery trout. We show that all populations have been strongly affected by stocking, with admixture proportions ranging from 14 to 64%. Historical population genetic structure was characterized by isolation by distance and by positive correlations between historical effective population sizes and habitat area within river systems. Contemporary population genetic structure still showed isolation by distance, but also reflected differences among populations in hatchery trout admixture proportions. Despite significant changes to the genetic composition within populations over time, dispersal rates among populations were roughly similar before and after stocking. We also assessed whether population declines or introgression by hatchery strain trout should be the most significant conservation concern in this system. Based on theoretical considerations, we argue that population declines have had limited negative effects for the persistence of adaptive variation, but admixture with hatchery trout may have resulted in reduced local adaptation. Collectively, our study demonstrates the usefulness of analysing historical samples for identifying the most important consequences of human activities on the genetic structure of wild populations.